Bahasa Inggris - Aprilianti Dwi Yuntiari; Pujiriyanto (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to determine the user experience of elementary school teachers in Samarinda City using the SSE application for evaluation learning media in terms of 6 aspects (attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty) as well as the responses, troubles, and feedback from teachers as users. The research uses a mixed method with sequential explanatory design, analyzing quantitative data through the User Evaluation Questionnaire (UEQ) and qualitative data through interviews. The results show that the teachers' experience level for the aspects of attractiveness (1.71), efficiency (1.74), stimulation (1.41), novelty (1.27) are included in the "Good" category and for the aspects of perspicuity (1.72) and dependability (1.22) are included in the "Above Average" category based on the result of quantitative data. However, several positive and negative responses were given based on the result of qualitative data which explains general troubles experienced by teachers are that not all teachers can operate technological devices, the application is considered quite confusing and less effective. Some feedbacks given by teachers explains that can be redeveloped in terms of features, provide technical guidance before used in schools. Still, in terms of its purpose, SSE application helping teacher performance in evaluating learning results.